Nitrous oxide emissions in Midwest US maize production vary widely with band-injected N fertilizer rates, timing and nitrapyrin presence - Burzaco JP; Smith, D.R.; Vyn TJ (IOP Publishing, 2013)
Nitrification inhibitors have the potential to reduce N2O emissions from maize fields, but optimal results may depend on deployment of integrated N fertilizer management systems that increase yields achieved per unit of N2O lost. A new micro-encapsulated formulation of nitrapyrin for liquid N fertilizers became available to US farmers in 2010. Our research objectives were to (i) assess the impacts of urea–ammonium nitrate (UAN) management practices (timing, rate and nitrification inhibitor) and environmental variables on growing-season N2O fluxes and (ii) identify UAN treatment combinations that both reduce N2O emissions and optimize maize productivity. Field experiments near West Lafayette, Indiana in 2010 and 2011 examined three N rates (0, 90 and 180 kg N ha−1), two timings (pre-emergence and side-dress) and presence or absence of nitrapyrin. Mean cumulative N2O–N emissions (Q10 corrected) were 0.81, 1.83 and 3.52 kg N2O–N ha−1 for the rates of 0, 90 and 180 kg N ha−1, respectively; 1.80 and 2.31 kg N2O–N ha−1 for pre-emergence and side-dress timings, respectively; and 1.77 versus 2.34 kg N2O–N ha−1 for with and without nitrapyrin, respectively. Yield-scaled N2O–N emissions increased with N rates as anticipated (averaging 167, 204 and 328 g N2O–N Mg grain−1 for the 0, 90 and 180 kg N ha−1 rates), but were 22% greater with the side-dress timing than the pre-emergence timing (when averaged across N rates and inhibitor treatments) because of environmental conditions following later applications. Overall yield-scaled N2O–N emissions were 22% lower with nitrapyrin than without the inhibitor, but these did not interact with N rate or timing.